Energy Consumption Effect on Economic Growth in Nigeria: Multivariate Framework - Abner Ishaku Prince; Inim, Izuchukwu Ogbodo; Eneoli Obinna Callistus; Udo, Emmanuel Samuel (International Journal of Economics, Management and Accounting, 2021)
This study analyzes the causal relationship between energy consumption and economic growth in Nigeria using the multivariate framework from 2000Q1-2018Q4, the Autoregressive Distributed Lag (ARDL) bounds test approach, Error Correction Model (ECM), and the Clemente-Montanes-Reyes unit root for structural breaks in the series. Findings revealed a co-integrating relationship, a bidirectional relationship between petroleum, liquefied natural gas, and electricity consumption. A unit increase in energy consumption stimulates economic growth through product and service value addition. A unit decrease in electricity consumption increases petroleum consumption while decreasing economic growth as a result of distribution failure, estimated billing system and over-dependence on generating set as an alternative energy source. The non-causal relationship can be accredited to the energy demand-supply gap. The study recommends among other things review of the billing system, pricing framework, and policies toward supporting and ensuring efficient and responsive energy distribution and maintenance to spur value addition and economic growth.